DEVELOPING SOFTWARE TO BUILD SUSTAINABLE FOREST MANAGEMENT PLAN IN BINH PHUOC PROVINCE - Quoc Hoan, Tran (Journal of Forestry Science and Technology, 2020)
Sustainable forest management software was developed by using Microsoft Visual C # professional 2010 with the help of Microsoft Access 2010 and Mapinfo Pro17.0 in 2020 in Binh Phuoc province with the overall goal to build a sustainable forest management plan for each forest owner from the map of sustainable forest management. The software has specific goals: (1) To update a forest protection and management map for the forest owner; (2) To synthesize thematic data on land management systems, planning of three forest types, forest origin, tree species, forest status, non-timber forest products… (3) To build a datasheet system as the requirement of a sustainable forest management plan. In which has land use plan, forest development plan, forest protection plan, forest product exploitation plan… (4) To determine options for forest management and use. (5) To export the output results in Excel and Word format. The software has been applied to build sustainable forest management plan for the period 2021 - 2030 for Ta Thiet Protection Forest Management Board and Loc Ninh Protection Forest Management Board in Loc Ninh district, Binh Phuoc province, with accurate results, high speed of treatment, large capacity, and stable. This software is installed and run independently on personal computers. In future, the software will contribute to support research and building sustainable forest management plan of forest owners.